2015
DOI: 10.3389/fpsyt.2015.00135
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Year Follow-Up Study of Attention-Deficit Hyperactivity Symptoms, Comorbidities, and Psychostimulant Use in a Brazilian Sample of Children and Adolescents with Attention-Deficit/Hyperactivity Disorder

Abstract: The aim of this study was to evaluate symptom persistence in attention-deficit/hyperactivity disorder (ADHD), the development of comorbidities, and psychostimulant usage patterns. Follow-up studies were conducted in 37 patients with ADHD and 22 healthy controls, aged 10 and 18, 4 years after their first assessment. The ADHD was rated as persistent if participants met all DSM-IV criteria for syndromic or sub-threshold persistence, or had functional impairments (functional persistence). Of the 37 ADHD patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In light of the evidence from pharmacovigilance studies, miltefosine usage has shown severe adverse reactions [170]. Furthermore, increasing incidence of miltefosine resistance has been seen even in PKDL cases [172]. The protracted treatment regimens invariably led to either nonacceptance or poor patient compliance.…”
Section: Classical Therapeutics Of Pkdl and Its Limitationmentioning
confidence: 99%
“…In light of the evidence from pharmacovigilance studies, miltefosine usage has shown severe adverse reactions [170]. Furthermore, increasing incidence of miltefosine resistance has been seen even in PKDL cases [172]. The protracted treatment regimens invariably led to either nonacceptance or poor patient compliance.…”
Section: Classical Therapeutics Of Pkdl and Its Limitationmentioning
confidence: 99%
“…ADHD is classified into three main types: inattentive, hyperactive-impulsive, and combined [ 3 ]. Generally, males are more likely to be affected by the disorder than females, with a ratio of 3:1 [ 4 ] in population-based studies and 4:1 in clinical studies [ 5 ]. However, the inattentive type is more common among females compared to males [ 6 ].…”
Section: Introductionmentioning
confidence: 99%